Does tertiary vocational education beat academic education? A matching analysis of young men’s earnings developments - Lukesch, Veronika [Verfasser]; Zwick, Thomas [Verfasser] (My University, 2020)
„This paper shows that young men who completed an apprenticeship education plus a tertiary vocational education have considerably higher earnings during the first half of their career than those who obtained an academic education in addition to their apprenticeship education. We match employees with a tertiary vocational and an academic education based on their labour market experience and their individual and employer characteristics during their formative apprenticeship training years in which they presumably decided on their further education track. Then we compare the earnings developments in both groups of the matched sample during their tertiary education phase and after its completion for maximally 16 years after apprenticeship completion. We use linked employer-employee data of the IAB (LIAB9310).“ (authors‘ abstract; BIBB-Doku)
Keywords: S 1.4 Hochschulbildung; S 1.5.2 Berufliche Weiterbildung; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; 370; Männer; Doppelqualifikation; Doppelqualifizierter; Hochschulabsolvent; Meister; Höhere Berufsbildung; Qualifikationsverwertung; Vergleich; Einkommensentwicklung